Antibacterial Activity of Rosmarinus officinalis against Multidrug-Resistant Clinical Isolates and Meat-Borne Pathogens. (29th April 2021) - Manilal, Aseer; Sabu, Kuzhunellil Raghavanpillai; Woldemariam, Melat; Aklilu, Addis; Biresaw, Gelila; Yohanes, Tsegaye; Seid, Mohammed; Merdekios, Behailu
Abstract : Background . In developing countries, the prevalence of bacterial infections is quite rampant due to several factors such as the HIV/AIDS pandemic, lack of hygiene, overcrowding, and resistance to conventional antimicrobials. Hence the use of plant-based antimicrobial agents could provide a low-cost alternative therapy. Rosmarinus officinalis is reputed as a medicinal plant in Ethiopia; however, its antibacterial activity against many of the clinical isolates remains overlooked. Methods . Tender foliage of R. officinalis was collected and extracted in ethanol (EtOH) and evaluated for their antimicrobial activity against ten multidrug-resistant (MDR) clinical isolates, human type culture pathogens, and meat-borne bacterial isolates by employing agar well diffusion assay. Results . EtOH extract of R. officinalis efficiently subdued the growth of all tested MDR clinical isolates in varying degrees. Salmonella sp. and Staphylococcus aureus were found to be the most sensitive clinical isolates. Likewise, it efficiently repressed the growth of meat-borne pathogens, particularly, S. aureus and Salmonella sp. showing its potentiality to be used as a natural antibacterial agent in the meat processing industry. The mechanism of antibiosis of plant extract against meat-borne pathogens is inferred to be bactericidal. Chemical constituents of the crude plant extract were analysed by Gas Chromatography-Mass Spectroscopy (GC-MS), Fourier Transform Infrared (FT-IR), and UV-visible spectroscopy showing genkwanin (26%), camphor (13%), endo-borneol (13%), alpha-terpineol (12%), and hydroxyhydrocaffeic acid (13%) as the major compounds. Conclusion . Overall results of the present study conclude that R. officinalis could be an excellent source of antimicrobial agents for the management of drug-resistant bacteria as well as meat-borne pathogens.